2020
DOI: 10.46588/invurnus.v15i2.24
|View full text |Cite
|
Sign up to set email alerts
|

Actitudes hacia la pandemia ocasionada por el coronavirus SARS-COV-2 y la COVID-19

Abstract: El objetivo del presente trabajo fue especificar un modelo para el estudio de las actitudes hacia los efectos de la pandemia sobre el medio ambiente. Se realizó un trabajo exploratorio, transversal y correlacional con 100 estudiantes, considerando su confinamiento y uso intensivo de tecnologías, dispositivos y redes electrónicas. Se encontró una estructura factorial de tres componentes; afectivo, cognitivo e intencional con siete indicadores cada uno sumando un total de 21 la cual explicó el 35% de la varianza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 4 publications
0
5
0
3
Order By: Relevance
“…These basic cognitive processes converge into three complex factors: information need, compatibility of skills with the accessibility and ease of use of technologies, and technology usefulness. Other studies have examined such convergence of the three factors and reported dimensions (measured using instruments) that refer to the impact of technology on the academia, college education, and professional training (Carreón-Guillén et al, 2020a). Although professors' job satisfaction can be the result of teaching and professional practice, positive experiences indicate that they also need to improve their skills and specialize in data management.…”
Section: Methods Designmentioning
confidence: 99%
“…These basic cognitive processes converge into three complex factors: information need, compatibility of skills with the accessibility and ease of use of technologies, and technology usefulness. Other studies have examined such convergence of the three factors and reported dimensions (measured using instruments) that refer to the impact of technology on the academia, college education, and professional training (Carreón-Guillén et al, 2020a). Although professors' job satisfaction can be the result of teaching and professional practice, positive experiences indicate that they also need to improve their skills and specialize in data management.…”
Section: Methods Designmentioning
confidence: 99%
“…The TCM maintains that people consume basic products and services through the consumption of secondary products. Individuals when buying a mobile phone or any product and technological information communication service, are exposed to the consumption of basic products and services that are advertised and sold through the technologies (Carreón, Espinoza and García, 2019). Therefore, the TCM argues that it is the perceptions of utility, innovation and efficiency that determine the consumption of products and services that are advertised and sold through the mobile phone.…”
Section: Theory Of Entrepreneurshipmentioning
confidence: 99%
“…El proceso de representación de la seguridad advierte, sin embargo, un aprendizaje continuo y permanente por parte de la ciudadanía, así como una retroalimentación con nuevos símbolos emitidos en los medios de comunicación y las redes electrónicas (Carreón et al, 2020). De este modo, gobernantes y gobernados construyen una agenda de seguridad pública que incluye ejes y temas de discusión permanentes y efímeros.…”
Section: Teorías De La Bioseguridad Y La Ciberseguridadunclassified
“…Por lo anterior, la ciudadanía puede derivar de la información circundante en los medios una postura ante el desempeño de sus autoridades y sus funcionarios; incluso, contrasta la información disponible con su experiencia de confinamiento, distanciamiento, contagio, enfermedad y muerte de personas conocidas (Carreón et al, 2020). Al establecerse un comparativo entre la comunicación de riesgos con sus experiencias, sus necesidades y sus expectativas, se genera un ecosistema de bioseguridad que al difundir sus emociones en redes electrónicas como Facebook, Twitter, WhatsApp, YouTube o Instagram construye una ciberseguridad.…”
Section: Introductionunclassified